Fabrication of foldable multifunction hand trolley / Muhammad Luqman Fahmi Mohd Zaki - Mohd Zaki, Muhammad Luqman Fahmi (2022)
Mechanical Engineering students of semester 4 were given a task to manufacture a product to help or ease people in solving everyday problems. From the data obtained, people are having a problem on carrying or transporting loads of bigger shape or dimensions. The objective of this project is to design and fabricate a multifunctional trolley and can be used with 4-wheel mode and 2-wheel mode. Other than that, this project is also to analyse the multifunction hand trolley affected to the applied load using simulation software. This concept will be generated by referring to existing products in the market based on the characteristic and criteria. Some manufacturing steps will be included in this proposal like research and literature review. There will be several manufacturing processes to fabricate this project like measuring, cutting, welding, and finishing. By the completion of this fabrication, an in-depth understanding will be gained and improvement on ability to write an excellent proposal for engineering design fabrication which then can assist fellow students in their future professional environment in engineering world.